2013
DOI: 10.1093/geronb/gbt033
|View full text |Cite
|
Sign up to set email alerts
|

Age Validation in the Long Life Family Study Through a Linkage to Early-Life Census Records

Abstract: It is possible to match a high fraction of older study participants to their early-life census records when detailed information is available on participants' family of origin. Such record linkage can provide an important source of information for evaluating age reporting among the oldest old participants. Our results are consistent with recent studies suggesting that age reporting among older whites in the United States appears to be quite good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…To ensure this, validation studies of age at cancer diagnosis or death must be carried out, especially among older populations. In the US, age misreporting among the oldest-old has been a concern, but several studies have found that age recorded on US death records is accurate also among the oldest individuals [15, 18]. A birth certificate is considered the gold standard for verifying an individual’s birth date, but for an old individual, the second best validation tool is often census data from the individual’s early life.…”
Section: Methodological Challenges In Studies Of Cancer In the Elderlmentioning
confidence: 99%
“…To ensure this, validation studies of age at cancer diagnosis or death must be carried out, especially among older populations. In the US, age misreporting among the oldest-old has been a concern, but several studies have found that age recorded on US death records is accurate also among the oldest individuals [15, 18]. A birth certificate is considered the gold standard for verifying an individual’s birth date, but for an old individual, the second best validation tool is often census data from the individual’s early life.…”
Section: Methodological Challenges In Studies Of Cancer In the Elderlmentioning
confidence: 99%
“…The aim of the LLFS is to identify genetic and phenotype traits that contribute to survival to extreme ages and subphenotypes of exceptional survival such as measures of healthy aging. Age reporting in the US LLFS sample has been shown to be of high quality [5]. Additional details about the LLFS such as phenotypic measures have been well described [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…In high-income countries (HICs), age misreporting affects primarily the oldest ages (Elo et al 2013) and/or the most disadvantaged groups. The reported age of centenarians has thus often been contested (Gessert, Elliott, and Haller 2002;Rosenwaike and Stone 2003).…”
Section: Age Misreporting In Demographic Studiesmentioning
confidence: 99%
“…In HICs, such issues with the quality of age data have been resolved through record linkages (Elo et al 2013). For some study participants, researchers seek to obtain independent, high-quality records of age for verification purposes.…”
Section: Age Misreporting In Demographic Studiesmentioning
confidence: 99%
See 1 more Smart Citation